Toxicological investigations in a fatal and non-fatal accident due to hydrogen sulphide (H2S) poisoning - Ventura Spagnolo, Elvira; Romano, Guido; Zuccarello, Pietro; Laudani, Antonino; Mondello, Cristina; Argo, Antonina; Zerbo, Stefania; Barbera, Nunziata (Forensic science international, 2019)
•Accidental hydrogen sulfide (H2S) exposure can determine fatal and non-fatal poisoning.•Thiosulphate is helpful in evaluation of H2S poisoning, except in fulminant death.•Low thiosulfate levels will be detected in blood and urine if death rapidly occurs.•High urine thiosulfate concentration indicates that H2S-related death slowly occurred. Hydrogen sulphide (H2S) is one of the most toxic natural gas and represents a not rare cause of fatal events in workplaces. We report here a serious accidental poisoning by hydrogen sulphide inhalation involving six sailors. Three of them died while the other three survived and were transported to the emergency room. No greenish discolouration of the body, that could be a feature of these type of deaths, was observed at autopsy. Given that blood and/or urine H2S detection does not allow to discriminate if it is related to inhalation or to putrefactive processes, the determination of thiosulphate, H2S main metabolite, is decisive. The succession of fatal events reported here can be rebuilt by toxicological data interpretation: the subject 1 died after a longer interval of time as demonstrated by the highest blood and urine thiosulfate concentrations; the subject 2 died after a short interval of time as showed by a lower blood and urine thiosulfate concentrations than subject 1; the subject 3 died almost immediately after H2S inhalation since he showed the lowest blood thiosulfate concentration, and no trace of sulphide and thiosulfate was found in the urine.